Poverty Reduction in Ghana—Progress and Challenges : Overview - Molini, Vasco; Paci, Pierella (World Bank, Washington, DC, 2015)
Ghana over the past two decades has enjoyed steady and robust growth, mainly through a modification in its economic structure: as the economy gradually shifted out of agriculture and into services, the country experienced noticeable advances in productivity. Agriculture's share of value added to GDP has declined at a faster rate since 2005, whereas the share of services has remained virtually unchanged. Employment has adjusted in line with the changes in the structure of the economy, with a progressive shift from the country side to urban areas. However, many challenges remain, in particular the fairly high share of the population still living in poverty and the persistent gender gaps in productive activities.